2021
DOI: 10.3390/foods10040896
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Action Mechanism Analysis of VvmiR156b/c/d-VvSPL9 Module Responding to Multiple-Hormone Signals in the Modulation of Grape Berry Color Formation

Abstract: In recent years, more and more reports have shown that the miR156-SPL module can participate in the regulation of anthocyanin synthesis in plants. However, little is known about how this module responds to hormonal signals manipulating this process in grapes. In this study, exogenous GA, ABA, MeJA, and NAA were used to treat the ‘Wink’ grape berries before color conversion, anthocyanin and other related quality physiological indexes (such as sugar, aroma) were determined, and spatio-temporal expression pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 55 publications
(47 reference statements)
0
13
0
Order By: Relevance
“…In fact, phytohormones play an important role in regulating the ripening process and secondary metabolism of grape berries. Previous studies have shown that the application of ABA, BRs and JA on grape berries before the color transition period can promote the accumulation of phenylpropanoid metabolites [17][18][19][20][21][22]. The spraying of IAA and Forchlorfenuron (CPPU) can delay the maturation process and change the flow of phenylpropane metabolic pathways [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, phytohormones play an important role in regulating the ripening process and secondary metabolism of grape berries. Previous studies have shown that the application of ABA, BRs and JA on grape berries before the color transition period can promote the accumulation of phenylpropanoid metabolites [17][18][19][20][21][22]. The spraying of IAA and Forchlorfenuron (CPPU) can delay the maturation process and change the flow of phenylpropane metabolic pathways [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to MYB and WD40 transcription factors and structural genes, SPL is also involved in the synthesis of anthocyanin. VvmiR156b/c/d‐mediated VvSPL9 participated in the formation of grape ( V. vinifera ) color in response to multi‐hormone signals (Su et al, 2021 ). The expression of VcSPL12 significantly enhanced the accumulation of chlorophyll and altered the level of expression of several genes associated with chlorophyll that are involved with the coloration of blueberry ( Vaccinium spp.)…”
Section: Discussionmentioning
confidence: 99%
“…color in response to multi-hormone signals (Su et al, 2021). The expression of VcSPL12 significantly enhanced the accumulation of chlorophyll and altered the level of expression of several genes associated with chlorophyll that are involved with the coloration of blueberry (Vaccinium spp.)…”
Section: Anthocyanin Content and Related Gene Expression In Purple Po...mentioning
confidence: 99%
“…The injected tobacco was kept in the dark for 2 d and the leaves were treated with water and 50 μM GA. On day three, leaves were collected. Each treatment was repeated with five leaves and the experiment was repeated three times (Su et al., 2021).…”
Section: Methodsmentioning
confidence: 99%